Impact of land reform programme in promoting agriculture development in Insiza district from 2002 to 2014 - Mugwara, Happiness (Midlands State University, 2017)
This study investigated the effects of The Zimbabwean Fast Track Land Reform in promoting agriculture development to mitigate poverty. The study targets the beneficiaries to establish the relationship between land reform programme and agriculture production and it is an assessment of how the beneficiaries of Insiza district have performed in terms of agriculture production after the implementation of the policy. The theoretical framework suggests the land of a nation is for the people and land is a panacea to the poverty crisis in rural communities. The researcher used the case study as the study design with data being collected using questionnaires and in-depth interviews. The study recognized the need of support from the government so to help the beneficiaries uphold the agricultural tradition of the nation at large in order to fight hard poverty. The study also established that there is too much political interference and also evidenced droughts that to an extent affect productivity in newly resettled farms. Therefore, the study recommendations that the government should by all means support the newly resettled peasants with farm inputs, it must provide with irrigation schemes or the resuscitation of irrigation infrastructure since the area have recorded trends of poor rainfall.